3-ACETYL -2,5,7-TRIHYDROXY-1,4-NAPHTALENEDIONE, AN ANTIMICROBIAL METABOLITE FROM THE CULTURE OF ENDOPHYTIC FUNGUS COELOMYCETES TCBP4 FROM Tinospora crispa - Praptiwi, Praptiwi; Jamal, Yuliasri; Fathoni, Ahmad; Nurkanto, Arif; Agusta, Andria (Media Penelitian dan Pengembangan Kesehatan, 2013)
Abstract Isolation, identification and testing of antimicrobial activity of secondary metabolites of endophytic fungal culture TCBP4 isolated from bratawali (Tinospora crispa) has been performed. The fungus TCBP4 was cultivated in Potato Dextrose Broth (PDB) for 1 month, media and fungi extracted with ethyl acetate. The extract was separated and purified by several chromatographic techniques, from which 9 fractions were obtained. Fraction 3e was purified again and was obtained 6 fractions (3e1-3e6). Fractions 3e3-3e6 were tested against bacteria isolates Staphylococcus aureus Bacillus subtilis,Eschericia coli and yeast isolate Candida albicans by microdillution method. Antimicrobial activity test result showed that fractions 3e3-3e5 had better antibacterial activity compared to chloramphenicol as commercial antibiotic. It was indicated by MIC value of the fractions was lower (8 ug/ml) compared with the antibiotic chloramphenicol (16 ug/ml). Fraction 3e3 had better antifungal activity compared to commercial antifungal nystatin and cabisidin against C. albicans. GC-MS analysis showed that the chemical constituent of 3e5 fraction was identified as 3-acetyl -2,5,7-trihydroxy-1,4-naphtalenedione . Key words : Tinospora crispa, endophytic fungi, isolation, identification, antimicrobial Abstrak Isolasi, identifikasi dan uji aktivitas antimikrobia terhadap metabolit sekunder dari kultur jamur endofit TCBP4 yang diisolasi dari tumbuhan bratawali (Tinospora crispa). Jamur endofit TCBP4 dikultivasi pada media Potato Dextrose Broth (PDB) selama 1 bulan, selanjutnya media dan jamur diekstrak dengan pelarut etil asetat. Ekstrak dipisahkan dan dimurnikan dengan beberapa teknik kromatografi sehingga diperoleh 9 fraksi. Fraksi 3e dimurnikan kembali dan diperoleh 6 fraksi (3e1-3e6). Fraksi 3e3-3e6 diuji aktivitas antibakterinya terhadap beberapa isolate bakteri Staphylo-coccus aureus Bacillus subtilis, Eschericia coli dan isolate khamir Candida albicans dengan metode mikrodilusi. Hasil uji antimikrobia menunjukkan bahwa fraksi 3e3-3e5 mempunyai aktivitas antibakteri lebih baik bila dibandingkan dengan chloramfenikol, dimana nilai MIC dari fraksi (8 ug/ml) lebih rendah dari antibiotika chloramfenikol (16 ug/ml). Fraksi 3e3 mempunyai aktivitas antijamur lebih baik bila dibandingkan dengan antijamur komersial nistatin dan kabisidin terhadap  C. albicans. Analisis GC-MS menunjukkan bahwa komponen kimia dari fraksi 3e5 diidentifikasi sebagai 3-acetyl -2,5,7-trihydroxy-1,4-naphtalenedione . Kata kunci : Tinospora crispa, jamur endofit, isolasi, identifikasi, antimikrobia